2020
DOI: 10.1111/medu.14360
|View full text |Cite
|
Sign up to set email alerts
|

Resident impression management within feedback conversations: A qualitative study

Abstract: Introduction Medical education is moving to conceptualise feedback as a bidirectional learning conversation. Within this conversation, learners experience a tension between assessment and feedback. That perceived tension affects learners’ outward performances. In this study, we aimed to characterise residents’ experiences with this tension and its effect on learner authenticity within feedback conversations. Methods In this constructivist grounded theory study, the authors were informed by Goffman's theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…He described that performance arises in two contexts: in the frontstage where ‘some aspects of the activity are expressively accentuated and other aspects, which might discredit the fostered impression, are suppressed’, 46 whereas in the backstage ‘the suppressed facts make an appearance’ 46 . Previous research on feedback conversations suggested how residents wanted to create a front stage performance to display confidence to supervisors 47 . While our results underline this finding, we also provide insights into the interplay between the frontstage and backstage.…”
Section: Discussionsupporting
confidence: 74%
“…He described that performance arises in two contexts: in the frontstage where ‘some aspects of the activity are expressively accentuated and other aspects, which might discredit the fostered impression, are suppressed’, 46 whereas in the backstage ‘the suppressed facts make an appearance’ 46 . Previous research on feedback conversations suggested how residents wanted to create a front stage performance to display confidence to supervisors 47 . While our results underline this finding, we also provide insights into the interplay between the frontstage and backstage.…”
Section: Discussionsupporting
confidence: 74%
“…By admitting our own limitations as educators, learners can better avoid the drive towards perfectionism and better accept that feedback is critical for growth. This would align with one participant's statement that they were more likely to incorporate feedback from an educator who demonstrates vulnerability than a ‘talking head or textbook walking around’ 3 . Additionally, imposter syndrome thrives in cultures where asking for help and identifying knowledge gaps are treated as a weakness 4 .…”
mentioning
confidence: 75%
“…This would align with one participant's statement that they were more likely to incorporate feedback from an educator who demonstrates vulnerability than a 'talking head or textbook walking around'. 3 Additionally, imposter syndrome thrives in cultures where asking for help and identifying knowledge gaps are treated as a weakness. 4 Therefore, we should normalise identifying knowledge gaps and encourage learners to focus on their growth as opposed to merely the achievement of goals.…”
Section: Residents Are More Likely To Incorporate Feedback From An Edmentioning
confidence: 99%
See 1 more Smart Citation
“…In residents receiving formative feedback, a growth mindset (contrasted with a fixed mindset) was associated with a focus on professional development, asking more questions, and looking for opportunities for growth. 16 A growth mindset has been associated with positive effects on the brain's neural network. 9 For institutional leaders, modeling a growth mindset 9,17 includes modeling transparency and self-compassion and an empathic response to patients and team members.…”
Section: The Growth Zonementioning
confidence: 99%